IMPACT OF TECHNOLOGY ON ENGLISH (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Technology has drastically transformed the world we live in, shaping every aspect of our daily lives. One area where technology has had a profound impact is the English language. With the rise of digital communication and the integration of technology into education, work, and social interactions, English has undergone significant changes and advancements. This article explores the various ways technology has influenced the English language.